2006
DOI: 10.1063/1.2226503
|View full text |Cite
|
Sign up to set email alerts
|

Photoreflectance-probed excited states in InAs∕InGaAlAs quantum dashes grown on InP substrate

Abstract: Photoreflectance (PR) measurements have been performed on InAs∕In0.53Ga0.23Al0.24As quantum dashes (QDashes) molecular-beam epitaxy grown on InP substrate. The PR features related to all relevant parts of the structure have been detected, including the ground and excited state optical transitions in QDashes. QDash ground state transition shifts from 1.5 to almost 2μm with the increase in the thickness of InAs layer, corresponding to the increase in the average size of the dashes. Excited state transitions have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
32
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 17 publications
4
32
0
Order By: Relevance
“…A similar temperature dependent carrier dynamics was also carried out by Jahan et al [194] on InAs/InAlAs Qdash heterostructure. Using PL and photo-reflectance (PR) measurements on a single Qdash layer embedded in InGaAlAs buffer layers, Rudno-Rudzinski et al showed the existence of ~2 ML thick wetting layer [195], observed the presence of ES at an energy of ~150 meV above the GS transition in Qdashes [196], and studied the interband optical transitions in DaWELL structure with InGaAs/InGaAlAs Qwells [197]. In addition, Podemski et al investigated the efficiency of excitons and free carrier injections in Qdash tunnel-injection structures via PL measurements [198] and measured Qwell-Qdash energy transfer up to 130 K employing PL excitation (PLE) study [199].…”
Section: Qdash Optical Propertiesmentioning
confidence: 99%
“…A similar temperature dependent carrier dynamics was also carried out by Jahan et al [194] on InAs/InAlAs Qdash heterostructure. Using PL and photo-reflectance (PR) measurements on a single Qdash layer embedded in InGaAlAs buffer layers, Rudno-Rudzinski et al showed the existence of ~2 ML thick wetting layer [195], observed the presence of ES at an energy of ~150 meV above the GS transition in Qdashes [196], and studied the interband optical transitions in DaWELL structure with InGaAs/InGaAlAs Qwells [197]. In addition, Podemski et al investigated the efficiency of excitons and free carrier injections in Qdash tunnel-injection structures via PL measurements [198] and measured Qwell-Qdash energy transfer up to 130 K employing PL excitation (PLE) study [199].…”
Section: Qdash Optical Propertiesmentioning
confidence: 99%
“…To emphasize the influence of confinement potential depth on the polarization properties of emission, we have compared the investigated structures with other elongated nanostructures-InAs/InGaAlAs/InP QDashes (LAR exceeding 5) [42][43][44][45]. Such InP-based structures exhibit much deeper confinement potential for both types of carriers, i.e., by definition expected to be much less sensitive to the peculiarities of the confining potential shape.…”
Section: A Degree Of Linear Polarization Of the Surface Emissionmentioning
confidence: 99%
“…One can see only a very weak PR feature at the PL peak energy, which is common for the QDash-related signal due to a small total absorption of a single QDash layer and their large intrinsic nonuniformity. 36 In contrast, pronounced PR resonances can be identified for all the samples at higher energies, related to optical transitions within the mixture of 0D-2D DOS. The energy of these transitions increases with d well , resulting in the decreasing spectral detuning between QW and QDash parts.…”
mentioning
confidence: 91%
“…The photoreflectance (PR) measures the change in the reflectivity spectrum upon photo-modulation, resulting in a derivative-like response, with clear signatures of optical transitions. 36 The PR was performed at both T = 5 K and RT, however, at low temperature the PR signal (not shown) cannot be separated from the PL signal dominating the overall spectral response. At T=300 K, the PL process constitutes only a background of the pronounced PR amplitude.…”
mentioning
confidence: 99%
See 1 more Smart Citation